2019
DOI: 10.1037/ccp0000391
|View full text |Cite
|
Sign up to set email alerts
|

Personality and outcome in individuals with treatment-resistant depression—Exploring differential treatment effects in the Tavistock Adult Depression Study (TADS).

Abstract: Objective: Although research over the past decades has investigated the impact of the personality dimensions of dependency and self-criticism on treatment outcome, little is known of how these personality features influence responsiveness to treatment in patients with severe, chronic forms of depression. Method: The present study uses data from the Tavistock Adult Depression Study (TADS), a randomized controlled trial investigating the effectiveness of long-term psychoanalytic psychotherapy (LTPP) compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…To place these findings in context, a discussion of the sample is warranted. Most recent outcome studies involving psychoanalysis (Knekt et al, 2011) and long-term psychoanalytic psychotherapy (e.g., Blatt, 1992;Knekt et al, 2017;Rost et al, 2019) have involved samples with greater levels of functional impairment compared to those in the present study. Despite patients in the present study having a better functional status, the sample also reflects individuals whose functional impairment improved following psychoanalysis, which lends support that patients in this study achieved functional gains after treatment.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…To place these findings in context, a discussion of the sample is warranted. Most recent outcome studies involving psychoanalysis (Knekt et al, 2011) and long-term psychoanalytic psychotherapy (e.g., Blatt, 1992;Knekt et al, 2017;Rost et al, 2019) have involved samples with greater levels of functional impairment compared to those in the present study. Despite patients in the present study having a better functional status, the sample also reflects individuals whose functional impairment improved following psychoanalysis, which lends support that patients in this study achieved functional gains after treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies support the notion that individuals with anaclitic and introjective depression differentially respond to treatment and usually do so in ways that are consistent with their underling personality organization (e.g., Blatt, 1992;Blatt & Felsen, 1993;Blatt & Ford, 1994;Blatt & Shahar, 2004;Rost et al, 2019). Individuals with anaclitic, or dependent/relatedness, dynamics will often experience intense longings for connection and emotional support and will have powerful worries about loss, separation, or abandonment.…”
Section: Therapeutic Change In Psychotherapy and Psychoanalysismentioning
confidence: 99%
See 1 more Smart Citation
“…• In addition, the level of severity of the personality dimension "dependency" may have a differential influence on the treatment outcome. Interestingly, a recent study investigated the impact on treatment outcome of the personality dimension dependency according to Blatt (54) in treatment-resistant chronically depressed patients and found that patients with more maladaptive dependent features did not benefit from a long-term psychoanalytic psychotherapy (LTPP) or treatment as usual (TAU), while those with less maladaptive dependent features showed considerable gains from LTPP but not from TAU (55). • The specific strategies of CBASP might trigger dependence on the therapist.…”
Section: Discussionmentioning
confidence: 99%
“…In a second study, Rost et al. (2019) found statistical and clinical significant differential treatment responses between these four groups of depressed individuals, calling for the need to tailor psychotherapy to individuals’ pre‐treatment personality features and functioning.…”
Section: Third Q‐tradition: the Californian Schoolmentioning
confidence: 99%